2007
DOI: 10.1128/ec.00091-07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Three Classes of Membrane Proteins Involved in Fungal Azole Resistance by Functional Hyperexpression inSaccharomyces cerevisiae

Abstract: The study of eukaryotic membrane proteins has been hampered by a paucity of systems that achieve consistent high-level functional protein expression. We report the use of a modified membrane protein hyperexpression system to characterize three classes of fungal membrane proteins (ABC transporters Pdr5p, CaCdr1p, CaCdr2p, CgCdr1p, CgPdh1p, CkAbc1p, and CneMdr1p, the major facilitator superfamily transporter CaMdr1p, and the cytochrome P450 enzyme CaErg11p) that contribute to the drug resistance phenotypes of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
230
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(242 citation statements)
references
References 67 publications
10
230
1
1
Order By: Relevance
“…The upregulations of multidrug efflux pump controlled by Cdr1p, Cdr2p belonging to ATP-binding cassette superfamily (APC transporter) and Mdr1p, a member of major facilitator superfamily (MFS) were implicated in most fluconazole-resistant C. albicans strains (Niimi et al 2004;Holmes et al 2012;Prasad and Rawal 2014) as FLC was a substrate for CDR1, CDR2, and MDR1 (Kohli et al 2001;Nakamura et al 2001). Rhodamine 6G was the most common used fluorescent dye of ABC pump substrate requiring ATP as energy to observe transporter-mediated FLC resistance (Lamping et al 2007;Peralta et al 2012). Our experiments showed that FLC alone failed to lead to rhodamine 6G accumulation in the intracellular space in C. albicans z2003 due to active efflux pump (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The upregulations of multidrug efflux pump controlled by Cdr1p, Cdr2p belonging to ATP-binding cassette superfamily (APC transporter) and Mdr1p, a member of major facilitator superfamily (MFS) were implicated in most fluconazole-resistant C. albicans strains (Niimi et al 2004;Holmes et al 2012;Prasad and Rawal 2014) as FLC was a substrate for CDR1, CDR2, and MDR1 (Kohli et al 2001;Nakamura et al 2001). Rhodamine 6G was the most common used fluorescent dye of ABC pump substrate requiring ATP as energy to observe transporter-mediated FLC resistance (Lamping et al 2007;Peralta et al 2012). Our experiments showed that FLC alone failed to lead to rhodamine 6G accumulation in the intracellular space in C. albicans z2003 due to active efflux pump (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the advanced genetics of S. cerevisiae, most studies of Cdr1p and Cdr2p have been carried out with heterologous expression systems in S. cerevisiae, where Cdr1p and Cdr2p were expressed under the control of a strong promoter, leading to very high levels of azole resistance (ϳ100-fold) (12,31). It was shown that the two transporters localize at the plasma membrane (35,37), bind rhodamine 6G (R6G) (12), export their substrates in an energy-dependent manner, and possess ATPase and phospholipid translocase activities (15,39). Expression systems in S. cerevisiae have also proved useful for structure-function studies of the transmembrane and ATPbinding domains of Cdr1p (14,26,31).…”
mentioning
confidence: 99%
“…First, the function of ABC transporters is influenced by their lipid environment (29,40) and, since S. cerevisiae and C. albicans have different plasma membrane lipid compositions (17,42), the function of Cdr1p and Cdr2p could be altered in S. cerevisiae. Also, the S. cerevisiae strains used for these studies carry deletions in (up to seven) genes which encode endogenous ABC transporters (12,15). Since these ABC transporters can function as sterol transporters or phospholipid flippases (8,27), the deletion of these genes may affect the plasma membrane composition of the recipient yeast and thus Cdr1p and Cdr2p function.…”
mentioning
confidence: 99%
“…Moreover, further functional assays confirmed that FK506 reduced the efflux of FLC. Additionally, another study indicated that FK506 can enhance the antifungal effect of FLC against a strain overexpressing the CDR1 gene in C. glabrata (Lamping et al, 2007). These results demonstrate that a combination of FLC and FK506 may act synergistically against C. glabrata at both the gene and protein levels.…”
Section: Discussionmentioning
confidence: 71%